1995
DOI: 10.1007/bf02506985
|View full text |Cite
|
Sign up to set email alerts
|

Organizational characteristics of empowering community settings: A multiple case study approach

Abstract: Although empowerment is often cited as a major guiding construct for community psychology, relatively little is known about the characteristics of empowering community settings. The current paper uses a multiple case study methodology to generate a number of key organizational characteristics of empowering community settings to guide future work in the area. In-depth, multilevel, longitudinal research was conducted on three empowering community settings: a religious fellowship, a mutual help organization for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
306
1
9

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(328 citation statements)
references
References 21 publications
(20 reference statements)
9
306
1
9
Order By: Relevance
“…As suggested in the social relationship and empowerment model, mutual support groups can be an important asset in developing such new relationships in an accepting social environment, and especially important if the families have been isolated by their problems related to caring for mentally ill patients (Borkman, 1999;Maton and Salem, 1995). Zimmerman (1990) and Perkins and Zimmerman (1995) have applied this idea in an organisational case study of GROW, a self-help community mental health movement for mentally ill populations in the United States (U.S.) and Australia.…”
Section: The Conceptual Basis Of Mutual Support Groupsmentioning
confidence: 99%
“…As suggested in the social relationship and empowerment model, mutual support groups can be an important asset in developing such new relationships in an accepting social environment, and especially important if the families have been isolated by their problems related to caring for mentally ill patients (Borkman, 1999;Maton and Salem, 1995). Zimmerman (1990) and Perkins and Zimmerman (1995) have applied this idea in an organisational case study of GROW, a self-help community mental health movement for mentally ill populations in the United States (U.S.) and Australia.…”
Section: The Conceptual Basis Of Mutual Support Groupsmentioning
confidence: 99%
“…During group meetings, each participant can also learn from others by exchanging caregiving experiences and information about mental illness (Asen, 2002). Maton and Salem (1995) applied the concepts of the psychological empowerment of individual participants and the social action process in a mutual support group in a case study on GROW, an international mutual support group network for mentally ill people that originated in Australia in 1957. They suggested that the empowerment of mutual support group members could be fostered by establishing a peer support system, inspiring individual members and providing them with opportunities to take on meaningful roles to be mutually supportive and strive for better mental health within group.…”
Section: Introductionmentioning
confidence: 99%
“…Maton's Organizational Characteristics Scale (Maton, 1988) used a Likert-type scale to measure perceptions of three organizational characteristics in community-based organizations: (a) leadership, (b) opportunity role structure, and (c) social support. First, the leadership subscale assessed the extent to which individuals with formal or informal responsibility within a group were interpersonally and organizationally talented, werer committed and dedicated to the organization, and supported and responded well to group members.…”
Section: Leadership Opportunity Role Structure and Social Supportmentioning
confidence: 99%